Hukum Wasiat yang Tidak Dilaksanakan Menurut Pendapat Imam Syafi’i - Mhd. Rajendra Abriman (ALADALAH: Jurnal Politik, Sosial, Hukum dan Humaniora, 2025)
A will in Islam is a person's last message which must be carried out after the death of the testator. Wills have a strong legal basis in Islamic law through the Koran, hadith and the views of ulama, including Imam Syafi'i. In his view, a will is a charity that takes effect after the death of the testator and must be fulfilled as long as it is in accordance with the Shari'a, such as not exceeding one third of the inherited assets without the consent of the heirs. This research aims to understand the legal obligations for implementing wills, the obstacles that often arise, the legal consequences of wills not being implemented, as well as solutions for dealing with these problems. The method used is a normative juridical approach with qualitative analysis supported by literature review and direct interviews in Tanjung Pura District, Langkat Regency. The research results show that the implementation of wills is often hampered by several factors, such as the heirs' lack of understanding of will law, family conflicts regarding the nominal or form of bequeathed assets, and the desire to control inherited assets. The consequences of a will not being implemented include violations of sharia, loss of certain heirs' rights, and prolonged conflict within the family. Settlement of cases in local communities is usually carried out through mediation by religious figures or institutions such as the Religious Affairs office, although some cases require formal legal intervention. This research provides recommendations for improving legal education, strengthening the role of religious institutions, and enforcing the law to ensure the implementation of wills in accordance with sharia and positive law in Indonesia.